Variation of antioxidant capacity and antiviral activity of the brown seaweed Sargassum filipendula (Fucales, Ochrophyta) under UV radiation treatments. Issue 1 (31st December 2022) - Polo, Luz K.; Chow, Fungyi
ABSTRACT: Physiological responses in seaweeds are influenced by environmental conditions such as UV radiation among other abiotic factors, concerns that must be taken into account for bioprospecting purposes. The production of UV-absorbing compounds is a well-known strategy for protecting organisms against UV radiation stress as the compounds absorb and dissipate short wavelengths. Besides their natural photoprotective sunscreen value, there is strong evidence of potential use as antioxidant, anti-inflammatory, antibacterial, antifungal, antimalarial, antiproliferative, immunomodulatory and anticancer agents. Here, we studied the relationship of potential cell damage to antioxidant activity and bioactive properties of brown seaweed Sargassum filipendula under the effect of radiation treatments: PAR (control), PAR+UVA and PAR+UVB after 10 days of exposure. Cell damage was assessed as DNA impairment by the quantification of cyclobutane pyrimidine dimers (CPDs). Antioxidant potential, tested by ABTS, DPPH, FRAP and chelating activity assays and quantification of total phenolic compounds were performed using methanolic crude extracts at different concentrations. Antiviral activity was assessed by the ability of different concentrations of methanolic and aqueous extracts to inhibit retroviral reverse transcriptase (RT) activity. PAR+UVB treatment negatively affected DNA integrity, and more CDP-DNA complexes were observed. Higher antioxidant activity was observed under PAR treatment than UVA and UVB radiation treatments. There was 25–90% inhibition of the RT enzyme for methanolic extracts, while aqueous extracts showed nearly 100% inhibition for all treatments and tested concentrations. UV-absorbing compounds in S. filipendula provide adaptive advantages against UV radiation exposure. Additionally, the species can be considered as a potential biotechnology source of natural bioactive compounds, and isolation of these compounds or obtaining bioactively rich extracts will potentially be of great benefit for the development of functional bioproducts.